2013
DOI: 10.5312/wjo.v4.i4.248
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of progressive strength training shortly after hip fracture surgery

Abstract: AIM:To investigate the feasibility of a 6-wk progressive strength-training programme commenced shortly after hip fracture surgery in community-dwelling patients. METHODS:This prospective, single-blinded cohort study evaluated 31 community-dwelling patients from four outpatient geriatric health centres aged 60 years or older, who started a 6-wk programme at a mean of 17.5 ± 5.7 d after hip fracture surgery. The intervention consisted primarily of progressive fractured kneeextension and bilateral leg press stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 50 publications
3
36
0
1
Order By: Relevance
“…This calls for an increased focus on ST for patients with trochanteric fractures, as strength deficits are associated with larger functional deficits after HF surgery in general [1,8]. …”
Section: Discussionmentioning
confidence: 99%
“…This calls for an increased focus on ST for patients with trochanteric fractures, as strength deficits are associated with larger functional deficits after HF surgery in general [1,8]. …”
Section: Discussionmentioning
confidence: 99%
“…The age of the participants and the distribution of fracture types are considered representative compared with individuals in other studies. 11 , 50 In addition, monitoring the use of pain medication and hip pain before, during, and after the test is considered a strength of this study because pain seems to infl uence the estimates obtained in a demanding performance test such as the 6MWT, 11 as confi rmed in the present study.…”
Section: Study Limitations and Strengthsmentioning
confidence: 91%
“…On the basis of a study conducted at a municipalitybased health care center, Overgaard and Kristensen 11 reported that hip fracture-related pain seems to infl uence performance in the 6MWT approximately 2 weeks after hip fracture surgery. Therefore, a later time point of 3 to 8 weeks postsurgery was chosen in the present study, and the participants attended outpatient rehabilitation at a municipality-based health care center.…”
Section: Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly it appears that progressive strength training should be started in hospital (83) and carried out into the rehab setting. A 6-week strength training program started after surgery was associated with decreased pain and an increase in 6-minute walk test speed (84). A 12-week resistance program resulted in improvements in gait speed, gait distance and self-rated health (85).…”
Section: Rehabilitationmentioning
confidence: 99%